2001
DOI: 10.1074/jbc.m105325200
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Inhibits Serum-stimulated Cell Proliferation and Enhances Serum-independent Cell Proliferation

Abstract: Independently of its role in lipid homeostasis, apolipoprotein E (apoE) inhibits cell proliferation. We compared the effects of apoE added to media (exogenous apoE) with the effects of stably expressed apoE (endogenous apoE) on cell proliferation. Exogenous and endogenous apoE increased population doubling times by 30 -50% over a period of 14 days by prolonging the G 1 phase of the cell cycle. Exogenous and endogenous apoE also decreased serum-stimulated DNA synthesis by 30 -50%. However, apoE did not cause ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…More relevant, LRP (next to ApoER2 and megalin) is a critical receptor for apoE, whose allelic status is a major risk factor for late-onset Alzheimer's disease (AD) (35) and other neurodegenerative disorders. Consistently, apoE-mediated functional modulation (potentially via agonistic binding of lipoprotein receptors) of cellular responses to mitogens as well as apoE-mediated inhibition of cell proliferation has been described (36). Recent work in mice also established LRP6 as critical co-receptor for WNT signal transduction (37,38,39) known to mediate cell differentiation, cell polarity, and cell adhesion.…”
Section: Discussionmentioning
confidence: 73%
“…More relevant, LRP (next to ApoER2 and megalin) is a critical receptor for apoE, whose allelic status is a major risk factor for late-onset Alzheimer's disease (AD) (35) and other neurodegenerative disorders. Consistently, apoE-mediated functional modulation (potentially via agonistic binding of lipoprotein receptors) of cellular responses to mitogens as well as apoE-mediated inhibition of cell proliferation has been described (36). Recent work in mice also established LRP6 as critical co-receptor for WNT signal transduction (37,38,39) known to mediate cell differentiation, cell polarity, and cell adhesion.…”
Section: Discussionmentioning
confidence: 73%
“…Apolipoprotein E can be produced in macrophages [20]. In a glioblastoma study, ApoE from macrophages was shown to be involved in the delivery of lipids to tumor cells and in the recycling of lipids by macrophages in necrotic areas [21].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional approaches to this problem have limitations and rely on simple qualitative assessments. Traditional methodologies that have been used to study macrophage apoE include characterizing the tissue distribution of apoE (11), measuring the effects of the endogenous synthesis of apoE vs. its complete absence (11), and measuring the effects of the endogenous synthesis vs. exogenous application of apoE (15,19). These methods are useful in comparative assessments, but they are unable to simultaneously quantify the serial effects mediated by apoE or other secreted biological mediators.…”
Section: Discussionmentioning
confidence: 99%